Direct Instruction Model to Increase Physical Science Competence of Students as One Form of Classroom Assesment - Hendrik Wenno (International Journal of Evaluation and Research in Education (IJERE), 2014)
Teacher as one important factors of the succes of the learning process, has an important role in learning. Teacher have to adapt the instructional design or model learning methods with the material to be taught. The purpose of the study was to determine the levl of student mastery on the concept of measurements throught direct instructioal model. Descriptive research with action in the class were used in this research to determinet the level of studet mastery on the measurement concept of the physical sciences in oreder to achieve competency. The samples were tweenty five of seventh grade of  student on the second semester of academic year 2012/2013 of 11th Ambon State Junior High School. The instrument used is the test items to measure mastery of concepts, namely (1) those items of performance tests to  measure proficiency in the use of measring tools made for teaching and learning activities takes place. (2) Those items daily tests to measure the level of mastery of the concepts of measurements. Total about thenty items with the form of objectie tests (multiple choice) with a score of 1 for a correct answer and 0 for a wrong answer). Data results of performance test to easure proficiency in the use of measuring tools were analyzed by calculating a qualitative descriptive () average, (b) standart deviation, (c) the range of the data, (d) number of classes, (e) the length of the class, (f) frequency distribution, (g) the median, (h) mode, whereas mastery of the concept data obtained through the daily tests, analyzed by quantitative descriptive. Performance tests scores and daily tests are converted into the category of excellent, goog, sufficient, and failed. The results showed that the level of student mastery of the material by measuring very good and well with the percentage of the final results of formative student tests, respectively 48.0 percent, and 44.0 percent. It can be concluded that the direct instructional model succesfully improve student learning outcomes, especially to the concept of measurement.DOI: http://dx.doi.org/10.11591/ijere.v3i3.6492